HYDROGEN ISOTOPE ANALYSIS OF REHYDRATED SILICIC LAVAS: IMPLICATIONS FOR ERUPTION MECHANISMS - DeGroat-Nelson P.J.; Cameron B.I.; Fink J.H.; Holloway J.R. (My University, 2001)
Bulk and step-heating hydrogen isotope measurements of glassy and vesicular samples from three young rhyolite lavas demonstrate for the first time that magmatic H2O can be distinguished from meteoric H2O added during rehydration. Step-heat extractions of gases obtained at five temperatures show that most meteoric H2O is released at around 400°C, while magmatic H2O comes off during the fusion step at 1100–1200°C. Magmatic H2O contents from vertically-arrayed lava samples show a downward increase consistent with the equilibrium pressure-dependence of H2O solubility. These gradients imply that volatile concentrations high enough to generate pyroclastic flows during front collapse may be found in the upper portions of silicic domes produced by relatively high eruption rates.